(untitled) (Polis (Santiago), 2018)
From some time up to these days, the so called Chilean model is jeopardized. The requirements of the chilean civil society become tangible on the streets of our country. The annoyance and, consequently, the social protest, has acquired increasing strength and adhesion among those who do not feel represented in the least neither by the State nor by the political class, generating thus different fronts of conflict, such as ecological activists, copper mining workers, secondary and university students, teachers and the Mapuche people among others, which has ended in the wide unpopularity and rejection of the present President of Chile, Sebastián Piñera. Nevertheless, the created dichotomy is interesting. While in the country’s internal front an historical social protest of proportions takes place, due to the wide gap of inequality, at the same time Chile reflects a forceful economy, whose macroeconomic indicators places it at the top in Latin America.